Aligned Electrospun Carbon Nanofibers as Electrodes for Vanadium Redox Flow Batteries. Issue 10 (1st August 2019) - Zhang, Zhihui; Bai, Bofeng; Zeng, Lin; Wei, Lei; Zhao, Tianshou
Abstract : Electrospun carbon nanofibers (CNFs) are regarded as potential electrode materials for vanadium redox flow batteries (VRFBs) due to the advantages of a large surface area and good electrochemical activity. However, woven CNFs with randomly distributed fibers are limited by poor permeability of the electrolyte, thus leading to a large mass‐transport polarization during battery operation. To address this issue, aligned carbon nanofiber (ACNF) webs are fabricated and applied in the battery with fibers parallel to the flow channel. Cyclic voltammogram results show that the as‐prepared aligned electrode exhibits better electrochemical activity for both the VO 2+ /VO2 + and V 2+ /V 3+ redox reactions than that of commercial carbon paper (CP) and random electrodes, attributing to its higher surface area and favorable surface activity. The battery with the ACNF electrode achieves higher voltage efficiency (87%, 60 mA cm −2 ) than that of CP and random electrodes. Moreover, the ordered structure of the aligned electrode further enhances mass transport effectively, thus lowering the concentration loss. The polarization curve measurements also show that the limiting current density of the aligned electrode is 25% higher than that of the random electrode. All these results demonstrate that the aligned electrode is promising in VRFBs. Abstract : The aligned carbon nanofiber electrode (ACNF) is prepared by an electrospinning method for higher performance of vanadium redox flow batteries (VRFBs). The ACNF electrode shows good electrochemical activity and reversibility for vanadium redox reactions. Moreover, the ordered structure of the ACNF enhances mass transport, thus lowering the concentration loss. Therefore, the battery with ACNF shows the highest efficiency and capacity.